Odpowiedź:
[tex]\begin{cases}\frac{x-1}{2}+\frac{y-1}{3}=1\ \ /\cdot6\\\frac{x-2}{8}-\frac{y-1}{4}=2\ \ /\cdot8\end{cases}\\\\\\\begin{cases}\not6^3\cdot\frac{x-1}{\not2_{1}}+\not6^2\cdot\frac{y-1}{\not3_{1}}=6\cdot1\\\not8\cdot\frac{x-2}{\not8}-\not8^2\cdot\frac{y-1}{\not4_{1}}=8\cdot2\end{cases}\\\\\\\begin{cases}3(x-1)+2(y-1)=6\\x-2-2(y-1)=16\end{cases}[/tex]
[tex]\begin{cases}3x-3+2y-2=6\\x-2-2y+2=16\end{cases}\\\\\\\begin{cases}3x-5+2y=6\\x-2y=16\end{cases}\\\\\\\begin{cases}3x+2y=6+5\\x-2y=16\end{cases}\\\\\\+\begin{cases}3x+\not2y=11\\x-\not2y=16\end{cases}\\---------\\4x=27\ \ /:4\\\\x=\frac{27}{4}\\\\\\Podstawiamy\ \ podana\ \ warto\'s\'c\ \ x\ \ do\ \ r\'ownania\ \ 3x+2y=11[/tex]
[tex]3\cdot\frac{27}{4}+2y=11\\\\\frac{81}{4}+2y=11\\\\2y=11-\frac{81}{4}\\\\2y=\frac{44}{4}-\frac{81}{4}\\\\2y=-\frac{37}{4}\ \ /:2\\\\y=-\frac{37}{4}\cdot\frac{1}{2}\\\\y=-\frac{37}{8}\\\\\begin{cases}x=\frac{27}{4}\\y=-\frac{37}{8}\end{cases}[/tex]